Efektivitas Double Track System atau Single Track System Bagi Pelaku Tindak Pidana Korupsi di Indonesia - Sulis Setyowati (Rechtsregel : Jurnal Ilmu Hukum, 2021)
The efforts to eradicate corruption in Indonesia are shown by the position of Indonesia as the most corrupt country in Asia, by the International Transparency Institute. The contributing factor is that the corruption eradication policy in Indonesia focuses more on the strategy of prosecution through penal means, so that the number of corruption cases that can be handled is far less than the number of potential criminal acts committed. This type of research is normative legal research which is commonly called normative juridical research using secondary data, namely data obtained from judge decisions, official document, related books, and related laws and regulations. This research uses a conceptual approach, a case approach, and a statute approach. Furthermore, the data is processed using descriptive analytical data analysis method. The result of research is the penal facilities that use the Criminal Procedure Code and Law Number 31 of 1999 as amended and supplemented by Law Number 20 of 2001 concerning Amendments to Law Number 31 of 1999 concerning Eradication of Corruption Crimes, have not been able to fully prosecute the perpetrators an increasingly sophisticated modus operandi of corruption. Therefore, it is necessary to measure the effectiveness level of implementing the double track system and single-track system.